2020
DOI: 10.3847/1538-4365/ab5e80
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study of Rate Coefficients for H2:H2 Inelastic Collisions between 295 and 20 K

Abstract: A laboratory study of state-to-state rate coefficients (STS rates) for H 2 :H 2 inelastic collisions in the v=0 state is reported. The study, which spans the 295-20 K thermal range, is based on the use of a kinetic master equation. It describes the time-space evolution of populations of H 2 rotational levels as induced by inelastic collisions. It is applied here to a supersonic jet of natural H 2 . This medium bears a large amount of relevant data that allows for the establishment of best values and confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…1. We note that Montero et al (2020) have made a limited comparison, for four rotationally-inelastic transitions, of the rate coefficients computed by Wan et al (2018) with empirically-derived values and found the theoretical rate coefficients to be lower than their measurements for temperatures 20 < T < 295 K. In a more recent study, Hernández et al (2021) compared experimental and theoretical rate coefficients for three rotationally inelastic transitions, induced by either H2(J = 0) or H2(J = 1), and found that the data adopted in the present calculations are generally in better accord with their measurements than those of Wan et al (2018).…”
Section: Calculations Of the Hcooling Function Wmentioning
confidence: 91%
“…1. We note that Montero et al (2020) have made a limited comparison, for four rotationally-inelastic transitions, of the rate coefficients computed by Wan et al (2018) with empirically-derived values and found the theoretical rate coefficients to be lower than their measurements for temperatures 20 < T < 295 K. In a more recent study, Hernández et al (2021) compared experimental and theoretical rate coefficients for three rotationally inelastic transitions, induced by either H2(J = 0) or H2(J = 1), and found that the data adopted in the present calculations are generally in better accord with their measurements than those of Wan et al (2018).…”
Section: Calculations Of the Hcooling Function Wmentioning
confidence: 91%
“…So far it has been successfully applied to free (i.e., unconfined) flows such as miniflames [149] or supersonic gas microjets of H 2 , N 2 , O 2 , CO 2 , H 2 O (gas) and some of their mixtures [150][151][152][153][154]. In N 2 [155], O 2 [156], and CO 2 [157,158] the temperature was determined through the rotational populations from the rotational Raman spectra, while in H 2 the rotational populations were measured from the rotationallyresolved vibrational Q-branch [159,160]. For H 2 O (gas), separate rotational lines in the vibrational Q-branch cannot be fully resolved, and the temperature was retrieved from the simulation of the Q-branch profile [161].…”
Section: Applicability To Gas Microflows and Current Limitationsmentioning
confidence: 99%